FLOATING HOUSE TECTONICS ON LAKE TEMPE: BETWEEN TRADITION AND RESILIENCE - Naidah Naing (Journal of Architecture&ENVIRONMENT, 2021)
The tectonic knowledge of the people who live in floating houses comes from the understanding of the tradition of building land on stilt houses because the fishing communities who live in floating homes also live on land. However, the climatic conditions above the water are extreme and different from the ground, causing the tectonics of the floating house to adapt to the climatic conditions on the water so that the floating house has resistance to natural disasters on the water. The problem of this research is that there is a change in the tradition of building from traditional mainland stilt houses to floating houses, thus creating a unique tectonic expression in floating homes. This study aims to reveal the tectonics of floating homes based on the tradition of building and surviving on the water. The research method used in this study is a qualitative method with an ethnic-architecture approach. The results showed that the tectonics of the floating house originating from the mainland stilt house tradition underwent changes in several parts, especially in the lower and middle structures. However, it does not change the concept of Bugis society's cosmology. Extreme climatic factors influence the formation of floating house tectonics. For the resilience of houses on the water, a structural system is needed to anticipate climatic conditions.